Uji Kelarutan Kristal Kalsium Oksalat Urin Tikus Sprague Dawley setelah Pemberian Eliksir Ekstrak Etanol Daun Pelawan (SOLUBILITY TEST OF CALCIUM OXALATE CRYSTAL IN SPRAGUE DAWLEY RAT URINE AFTER GIVING ETHANOL EXTRACT OF PELAWAN LEAVES) - Januar, Rahmawati; Wientarsih, Ietje; Widhyari, Sus Derthi (Jurnal Veteriner; Vol 21 No 1 (2020), 2020)
Traditional medicine is an herbal medicine used from generation to generation by people in Indonesian. Pelawan leaves is believed can dissolve crystals in the urine that can be the initial cause of kidney stone formation. This study aimed to evaluate the potential of elixir of the ethanol extract of pelawan leaves as antilithiasis in rat was given ethylene glycol and ammonium chloride as inducer. Thirty male rat Sprague dawley was divided in five different groups (n=6). The control group (K1), ethylene glycol (EG) and ammonium chloride (AC) as inducer (K2), inducer and Batugin 5,4 mg (K3); inducer and the elixir of the ethanol extract ofpelawan leaves (EEEDP) 100 mg/kg body weight (K4) and 200 mg/kg body weight (K5). The treatments were done in 28 days with urines observated at day 14 and day 28. The result showed that pelawan contain flavonoid, tannin, saponin and steroid. The result showed that treatment groups dissolved calcium oxalate crystals. Observated at day 14, K3 dissolved calcium oxalate crystals with lowest number, while at day 28, K4 dissolved calcium oxalate crystals with lowest number. A dose of 100 mg/kg body weight in the K4 group effectively dissolves the calcium oxalate crystals.